مجالس الإملاء الحديثية في العصر السلجوقي وأمالي نظام الملك: دراسة تحليلية: Hadith Dictation Sessions in the Seljuk Era and the Amālī of Niẓām al-Mulk: An Analytical Study - Dogan, Muhammed Furkan; Bannga Ahmed Ali, Ahmed El-Mogtaba (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يتناول هذا البحث مجالس الإملاء الحديثية خلال العصر السلجوقي، وينطلق من إشكالية مركزية تتعلق بكيفية إسهام الدولة، ممثلة في شخصية الوزير نظام الملك، في دعم هذه المجالس وتحويلها إلى مؤسسات تعليمية رسمية. ويهدف إلى بيان دور نظام الملك في حفظ الحديث النبوي ونشره من خلال مشاركته المباشرة في إملاء الأحاديث، وتحليل الأثر الذي أحدثه في هذا المجال. وقد اعتمدت الدراسة المنهج التحليلي الوصفي، حيث تم تحليل كتاب الأمالي المنسوب إلى نظام الملك، مع دراسة منهجيته في اختيار الأحاديث وإملائها، ومصادره الحديثية مثل صحيح البخاري وصحيح مسلم، واهتمامه بتوثيق الروايات وبيان صحتها. وتوصل البحث إلى أن العصر السلجوقي شهد ازدهارًا علميًا بدعم الدولة للعلوم الإسلامية، لا سيما الحديث، عبر إنشاء المدارس النظامية. وقد تميز نظام الملك بين رجال الدولة بدوره الفعّال في هذه المجالس، إذ لم يكن راعيًا فحسب، بل كان محدثًا يُملي الأحاديث بنفسه، مما انعكس بوضوح في كتابه الأمالي الذي ضم أحاديث أملاها بحضور العلماء والطلاب. ABSTRACT This research addresses a central problem concerning how the Seljuk state, particularly through the figure of Niẓām al-Mulk, contributed to supporting and institutionalizing Hadith Dictation Sessions (Majālis al-Imlā’ al-Ḥadīthiyya). The study aims to highlight Niẓām al-Mulk’s pivotal role in preserving and transmitting Hadith by actively participating in the dictation process and to assess the influence he exerted on the structure and function of these sessions. To achieve this, the study employs a descriptive-analytical method. It analyzes Niẓām al-Mulk’s Amālī (dictations) by examining his methodology in selecting Hadiths, his reliance on authentic sources such as Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim, and his efforts in verifying the narrations and their chains of transmission. The findings reveal that the Seljuk era witnessed a remarkable intellectual flourishing supported by state sponsorship of Islamic sciences, especially Hadith. The establishment of Nizamiya schools as major centers of transmission played a key role. Niẓām al-Mulk was unique among statesmen for his active engagement in these sessions—not merely as a patron, but as a transmitter of Hadith himself. This is clearly reflected in his Amālī, which contains narrations he dictated in the presence of scholars and students.